Digressions and the human imagination
1 online resource.
Keywords: "Digressions and the Human Imagination makes a significant contribution to our anthropological knowledge about human creativity. The creative force of the human imagination is widely considered as a key ingredient in understanding how social and cultural transformations occur. And yet, what we know about the nature of creative processes is surprisingly limited. Taking their cue from literary studies, the contributors to this volume explore digression as human creativity's main impulse. They offer a series of experimental explorations of digression in different arenas of social life - literature, conversations, myths, humor, art, wayfinding. In their examination of the relationship between creativity and digressive processes, the contributions challenge and eventually collapse conventional distinctions between 'artistic' and 'scientific' imaginaries. The book articulates with clarity the freedom and joy of wandering off in new directions, but also the potentially transgressive and even revolutionary character that digression has when it is put to work through the creativity of the human imagination. It will be relevant for anthropologists and other scholars from across the humanities and social sciences with an interest in creativity"--